Peran Tata Usaha dalam Pengelolaan Arsip di Madrasah Tsanawiyah Negeri 4 Bungo - Astika, Yulia Wiji; Poiran, Poiran; Stianingsih, Ani (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this research was to determine the role, constraints, and efforts of the Administration MTs N 4 Bungo in managing of archives. The type of research used was descriptive method with a qualitative approach. The population in this research were employees at the MTs N 4 Bungo. The unit of analysis consists of 6 people with a purposive sampling technique. The collection of research data was carried out by means of field studies in the form of interviews, observation, and documentation. Based on the results of research at MTsN 4 Bungo, the management of archives carried out at Madrasahs is still untidy and greatly affects the retrieval of archives. Archives are stored around the workspace, some are even on tables and on the floor because they don't have file shelves, the room is too cramped, giving the impression that the archives are not well maintained. Archive storage facilities are lacking, there are still several facilities such as archive cupboards that have not been organized due to limited space. Some of the obstacles faced include problems in maintaining archives and the lack of archive storage facilities. Efforts are being made to maintain, arrange, and maximize infrastructure facilities to support archive storage